Perubahan Tutupan Hutan Di Taman Hutan Raya Wan Abdul Rachman (Tahura War) - Handoko Handoko; Arief Darmawan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Changes in forest cover due to land tenure is a serious threat to Great Forest Park Wan Abdul Rahman. This study aimed to analyze changes in forest cover in 1994, 1997, 2000, 2014, and the things that happen related to changes in land cover in Great Forest Park Wan Abdul Rahman. Techniques of remote sensing and geographic information systems used to monitor and evaluate changes in forest cover that have occurred since the year 1994 - 2014 and determine forest cover changes that occur in each block management. Landsat satellite image data in 1994, 1997, 2000, 2014 were collected and analyzed. Furthermore, direct observation in the field is done for assessment of accuracy as well as the literature study to look at the chronology of events related to the change of the forest. The results showed forest area in 1994 was 9,090.1 hectare or 40.9% of the total area Great Forest Park Wan Abdul Rahman. In 2000 the highest forest cover has decreased be 5,428.7 hectare or 24.4% of the total area. 2014 forest cover has increased to 8.953 hectare or 40.2% of the total area. Keywords: classification image, land cover change, Great Forest Park Wan Abdul Rachman